A Study on the Effect of Shoulder Stability Exercises and Stretching Exercises in Shoulder Impingement Syndrome Among Adult Population - Lokesh R (Journal of Medical Biomedical and Applied Sciences, 2021)
BACKROUND OF THE STUDY: Shoulder pain is a result of rotator cuff pathology; it is a second most common musculoskeletal condition that causes shoulder pain in the general population. Shoulder muscle imbalance and posterior capsule tightness have been implicated as contributing factors. AIM OF THE STUDY: To find the effect of shoulder stability exercise and stretching exercise on disability status in shoulder impingement syndrome. METERIAL AND METHOD: 30 patients were recruited and equally dived into two groups. Group A(Stability exercise), Group B(Stretching exercise).The subjects in the both groups were examine for functional status through shoulder pain disability index, range of motion, and numerical pain rating scale for before and after intervention. The intervention period was 4 weeks. RESULT: The result shows the outcome of Group A with a P- value of 0.000(<0.05) and Group B with a P- value of 0.000(<0.05) but Group A statistically significant improvement than Group B.CONCLUSION: Stability and Stretching exercise were significantly improves the functional status, ROM, and reduces the pain. Compare with stretching exercise stability exercise are more effective.